Bringing context and structure back into situated learning. Issue 1 (February 2014) - Hotho, Jasper J; Saka-Helmhout, Ayse; Becker-Ritterspach, Florian
Practice-based studies have progressed thinking in the knowledge, learning and innovation fields by emphasizing the continual negotiation of social structures and meaning through participation. Yet, only a few contributions discuss how participation and learning are affected by broader structures. This is an inconsistency in the understanding of 'situated' learning where learning through participation is restricted to the immediate community involved in a social activity. We aim to address this inconsistency by investigating the effects of the interplay between institutional and organizational structures on patterns of participation and, in turn, learning outcomes. We develop a framework of situated learning in multinational enterprises, and explore its value through a comparative case study of the introduction of new practices in four subsidiaries of two multinational enterprises in two contrasting national institutional systems.In contrast to older views, our case findings suggest that while the interplay between institutional context and organizational structure indeed matters, it does not determine collective participation and situated learning as actors can actively create solutions when structural conditions and institutioanl demands are less aligned.